On approximate solution of the Dixon integral equation and some its generalizations - Barseghyan, A. G. (Computational mathematics and mathematical physics, 2017)
The paper is devoted to the study and numerical analytical solution of Fredholm-type integral equations of the second kind with symmetric kernels represented by homogeneous functions of degree (-1). The well-known Dixon equation and some its direct generalizations are specially considered. The equations are solved by passing to a Wiener–Hopf equation and applying the kernel averaging method. Results of numerical calculations are presented.